Interpretasi Ma’na Cum Maghza terhadap Azab Pelaku Homoseksual - Fauzuni Kurnia Okta; Toni Markos; Mhd Idris (Jurnal Ulunnuha, 2023)
This article aims to explore the significance of Qur'an Surah al Qamar verses 37-39 on the punishment of homosexual offenders. The homosexual phenomenon that exist today has basically been banned since the time of Prophet Lot because it is against religion and is considered to have exceeded his nature as a human being. This research is a literature research using ma'na cum maghza theory as the analysis tool. This theory is an alternative reading method to adjust between the original meaning (divine) and the main message (insaniyah). The results of this study indicate that the historical meaning (al ma'na al tarikhi) of lafazh azab in the Qur'an Surah al-Qamar 37-39 is wide and not monotonous. Historical phenomenal significance (al maghza al tarikhi) in these three verses explains that Allah gives orders for each of his servants to always obey and not commit heinous acts that violate Islamic law and Allah will give punishment to those who violate the orders and laws. While the main message of dynamic phenomenal significance (al maghza al mutaharrik al-ma'shir) that this verse was revealed by Allah as a warning to homosexual offenders so that they no longer commit heinous acts that violate Islamic law and the punishment that Allah sends down as proof that Allah's warnings and sanctions are real.